If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(2x + 5) = 37 Reorder the terms: 5x + 2(5 + 2x) = 37 5x + (5 * 2 + 2x * 2) = 37 5x + (10 + 4x) = 37 Reorder the terms: 10 + 5x + 4x = 37 Combine like terms: 5x + 4x = 9x 10 + 9x = 37 Solving 10 + 9x = 37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 9x = 37 + -10 Combine like terms: 10 + -10 = 0 0 + 9x = 37 + -10 9x = 37 + -10 Combine like terms: 37 + -10 = 27 9x = 27 Divide each side by '9'. x = 3 Simplifying x = 3
| 294b^2-150= | | 105b^2+10ab-24a^2b= | | x^2+20x-12000=0 | | x-(-3x+8)=4 | | 15/3-4i | | 100x=15 | | 5(x-17)=-2(x+14) | | 10x-x=14 | | 100x-10x=108 | | 100x-10x=11 | | 7a+23=3 | | x(5x^2+10x-15)=0 | | y=px+a | | y=px | | 0=6x^2+10x-16 | | 6(5x+2)=36x+10-2(3x-6) | | 13-3y+3y=15 | | 4(x)2=100 | | 16x+11y=120 | | (1-7z)(5)= | | (x+0.34)(x+.23)=2 | | X^4+116x^2+1600=0 | | -3x+3y-12=0 | | (-4-3b)(-8)= | | 8x-4=7x-9 | | 2(4x+7)=-47+53 | | 3.50/103.5 | | -3x+23=5-2(x-4) | | 5x-19=-34 | | g(-5b)=4x+3 | | 5x-19=34 | | (2x+3)(x^2+1)=(-3x-7)(x^2+1) |